2012
DOI: 10.5923/j.ijap.20120204.04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prior Victimization and Socio-Economic Status on People’s Crime-Reporting Behavior

Abstract: The purpose of this study is to determine whether or not prior victimizat ion, along with socio-economic status affect people's willingness to report crimes to authorities. This study is limited to addressing the effect of prior v ictimization on willingness to report crimes by 1) the type of victimizat ion (i.e., being a v ictim of property crimes or a victim o f crimes against persons), 2) being a vict im of a crime, regardless of the type of crime versus not being a victim, and 3) the difference in crime-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Research has consistently shown women from lower socio-economic backgrounds are more likely to engage in criminal activity than women from higher socio-economic backgrounds 28 . This disparity may be due to a number of factors, including limited access to education and employment opportunities, higher rates of poverty and unemployment, exposure to criminal networks and an environment encouraging criminal behavior 29 .…”
Section: Factors Affecting Women's Criminality Socioeconomic Factors -mentioning
confidence: 99%
“…Research has consistently shown women from lower socio-economic backgrounds are more likely to engage in criminal activity than women from higher socio-economic backgrounds 28 . This disparity may be due to a number of factors, including limited access to education and employment opportunities, higher rates of poverty and unemployment, exposure to criminal networks and an environment encouraging criminal behavior 29 .…”
Section: Factors Affecting Women's Criminality Socioeconomic Factors -mentioning
confidence: 99%
“…Crime-reporting action is generally regarded as a manifestation of a willingness to report crimes to authorities (Avdija & Giever, 2012). According to a review of the existing research on crime-reporting behavior, people's readiness to report a crime to the police is influenced by a number of interconnected factors.…”
Section: Introductionmentioning
confidence: 99%